(untitled) (International Journal of Studies in Nursing, 2025)
Background: Empowering nurses with a skill to understand problems from a person centered perspective is essential in addressing complex health challenges. HCD is a creative approach to problem-solving that focuses on understanding the needs and experiences of the people who will use a product or service. HCD can be seen as a tool and process for achieving the higher stages of patient engagement. Method: This case study, showed how nursing students were able to use Human Centered Design approach, after the introduction of HCD, into a community health project. The students integrated the five phases of HCD: Empathize, Define, Ideate: Prototype, Test to identify and co-build strategy with adolescent mothers to educate on life skills of interest. Result and Conclusion: Adolescent mothers need educational support on stress management, breast feeding and time management to enable them to successfully navigate motherhood demand.